Urgensi Seni Rupa Kaligrafi Dalam Pendidikan Islam - Nurul Hidayah Puji Lestari; Yazida Ichsan; Rachmat Sukriyanto; Saas Asela (PALAPA, 2021)
Islamic Religious Education aims to form the Islamic personality of students in accordance with Islamic law who believes and upholds monotheism.Many methods in learning can be used to help educators achieve the goals of education, but rarely use works of art or practice using these works of art in terms of learning Islamic religious education, one of which is the art of calligraphy Calligraphy art is included in the fine art of writing beautifully where the writing is adjusted to predetermined rules. In addition, of course, it has also been explained what the laws of this art are in Islamic law. But what if this art is used for The learning process for the realization of the goals of education will be discussed in this article. This study uses the literature review method, with the aim of describing the urgency of the art of calligraphy in learning Islamic education. This aligraphy can help the learning process of Islamic Religious Education to form Islamic characters in accordance with Islamic law.